Association of autism spectrum disorders and gastrointestinal infections in children. (September 2021) - Heisel, Matthew; Susi, Apryl; Short, Patrick; Rogers, Philip; Hisle-Gorman, Elizabeth; Gorman, Greg; Nylund, Cade
Highlights: Children with autism spectrum disorders (ASD) are more likely to be diagnosed with gastrointestinal infections than children without ASD. Daily living skill interventions such as hand-washing might mitigate the risk of gastrointestinal illness in ASD. Identifying an association between ASD and gastrointestinal infections adds a potential way to improve the health of patients with ASD. Background: Children with autism spectrum disorders (ASD) have differences in daily living skills such as motor skills and hand hygiene which may put them at increased risk for gastrointestinal infections. The risk of enteric infections in this population is unknown. The intention of this study was to determine if there is an association between a diagnosis of ASD and various infectious gastrointestinal diseases in children. Methods: This study is a retrospective, matched case-cohort study of children aged 2–18 years, enrolled in the TRICARE Military Health System database between October 2000 and September 2013. Each child diagnosed with ASD was matched to five controls by age, gender, and enrollment time frame. Various gastrointestinal infections were identified using ICD-9-CM diagnosis codes. Associations were evaluated using conditional logistic regression. Results: There were 48, 762 children with ASD and 243, 810 controls. 7834 (16.1 %) of children with ASD and 28, 499 (11.7 %) controls had infectious gastroenteritis. Children with ASD had increased odds (95 % Confidence Intervals) of Salmonellae (1.61 (1.26–2.07)), Shigellosis (1.53 (1.08–2.17)), Escherichia coli (1.79 (1.34–2.40)), other bacterial enteritis (2.06 (1.61–2.64)), other bacterial food poisoning (1.41 (1.08–1.84)), viral gastroenteritis (1.44 (1.39–1.48)), protozoa (1.60 (1.28–2.01)), helminth (1.44 (1.34–1.54)), and Helicobacter pylori (1.94 (1.54–2.43)) enteral infections compared to children without a diagnosis of ASD. Conclusions: Our study shows an association of a variety of gastrointestinal infections with children who were previously diagnosed with autism spectrum disorder. This association underscores that value should be placed on interventions that mitigate the risk of gastrointestinal illness among those with ASD.